TEACHER CERTIFICATION IN INDONESIA: A CHALLENGE FOR ELEMENTARY SCHOOL TEACHER PROFESSIONALISM - Rahayu, Nanik Sri (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
As the most important school level among the others, elementary school has become the main concern of societies since it serves as the basis for the foundation of education for the children. To achieve qualified teaching learning process in this level of education, it must be supported by qualified teachers too. If the teachers don’t have professionalism, they may contribute to the students’ misfortune in the future. However, nowadays in reality, the quality of public elementary school is still being questioned. There are two factors influencing this phenomena (1) insufficient professionalism of the teacher, and (2) low monitoring. In this context, as the certified civil servant teacher in elementary school, teachers should improve their professionalism as mandated by Teacher Law.